Can creative activities and mind-body practices help enhance well-being and mental health awareness? An exploratory qualitative study in UK higher education - Marianna Cortesi; Federico Pendenza; Elizabeth Haddon; Andrea Schiavio (PLoS ONE, 2025)
Creative arts activities and mind-body practices, such as yoga, have been shown to benefit mental health and well-being. Research in higher education highlights the mental health challenges faced by students and staff in tertiary education; however, most studies on the potential of creative arts and mind-body practices have been conducted in the United States, with limited research investigating their impact in the UK higher education context. This qualitative study seeks to examine students’ and staff members’ views on extra-curricular creative and mind-body practices provided by one UK university, exploring how engagement in such activities can impact their understanding and awareness of mental health and well-being. In addition, it intends to investigate potential barriers to engagement with such activities. Drawing on questionnaire responses from 25 students and 20 staff members, findings highlight the effectiveness of art-based interventions and mind-body practices in raising awareness and understanding of mental health and well-being, while also having the potential to positively impact individuals’ mental health and well-being. Although personal interests and time restrictions may limit engagement, such activities were found to foster community-building, a particularly relevant factor in the post-Covid era, as institutions seek to re-engage students and staff through in-person activities. These findings have therefore important implications for the implementation of similar interventions in higher education and beyond to promote mental health and well-being awareness in diverse communities.